Parâmetros metabólicos, ventilatórios e cardiovasculares durante a realização de atividades funcionais em indivíduos com doença de Parkinson - Raquel de Carvalho Lana (2015)
Although the daily physical activity pattern in the early stages of Parkinson's disease (PD) appears to be similar to that of controls, it tends to change with the progression of the disease. Recent research observed that individuals with PD are 29% less active than healthy individuals. In addition, due to the bradykinesia, individuals with PD tend to reduce the quantity and variety of regular physical activity. Understanding the factors related to the reduction of the physical activity level is of major importance in the management of PD complications. The exercise capacity of individuals with early-stage PD can be comparable to that of individuals without the disease when the subject involved maintain a certain level of regular physical activity. However, reaching aerobic peak occurs in a significantly lower level of exercise (lower speed, lower intensity or shortest time) indicating a lower energy efficiency. Data indicate that individuals with PD spend approximately 20% more energy than age- and sex- matched healthy individuals during exercises with similar load. Taking into account such findings in the literature, three objectives were outlined in this thesis: (a) investigate the determining factors of the physical activity level of individuals with PD; (b) investigate whether the Stair Ascent and Descent Test (TE) and the 6-minute Walk Test (6MWT) can be used in the evaluation of physical capacity of patients with PD and (c) to investigate whether there is a difference in energy efficiency of individuals with PD, when compared to individuals controls matched by age, sex and physical activity level. Initially, 46 individuals (66 ± 12 years) were recruited to investigate the determinants of the physical activity level of individuals with PD, using the Human Activity Profile (HAP). Through linear regression analysis, two models that explained 76% of the variance of HAP were observed. The first comprises age, ability to perform Activities of daily living (ADL) and HY modified scale; and the second comprises age, ability to perform ADL, and bradykinesia. Among the PD patients recruited, 20 (62 ± 8 years) participated in the subsequent studies. The variables number of steps climbed during five minutes of the ST (steps) and distance of the 6MWT were able to predict 36% and 41% of peak oxygen expenditure (VO2 peak) of a Cardiopulmonary Exercise Test (CPET). Steps and time spent for one ascent and descent (time) of the ST and distance and speed of the 6MWT were able to discriminate between individuals with different functional levels according to the HAP and the motor part of the Unified Parkinson's Disease Rating Scale (UPDRS). The TE was considered vigorous intensity test, while the 6MWT presented moderate intensity. Subsequently, such individuals were matched to controls and the difference in oxygen expenditure, other cardiorespiratory parameters (heart rate HR, respiratory exchange ratio - RER, ventilatory equivalent - VE/VCO2, oxygen pulse - VO2/FC and double product) and clinical parameters of the CPET (time, speed and inclination), ST (time, steps, distance) and 6MWT (distance and speed) were evaluated. Submaximal exercise tests' energy cost was calculated by dividing the VO2 peak of tests by distance. The VO2 peak of CPET, ST and 6MWT were similar between groups. The CPET' speed and inclination reached at peak exercise were higher in the control group (CT). In the ST, the time was lower in the CT group and steps and distance were greater. In the 6MWT, distance and speed were higher in the CT group. Energy cost value in the ST was higher in the PD group, showing that such individuals spend more energy per meter traveled than controls. Modifiable factors such as ability to perform ADL and bradykinesia have been identified as predictors of physical activity level of individuals with PD. Clinical variables of the ST (vigorous intensity) and the 6MWT (moderate intensity) were able to partially predict maximal exercise capacity and discriminated PD individuals with different functional levels. With the use of submaximal exercise tests as the ST and the 6MWT, assessment of exercise capacity and functional performance can be included in the rehabilitation process of PD. Finally, individuals with PD presented reduced energy efficiency during functional submaximal activities such as stair ascent and descent and overground walking.